On the membrane translocation of diphtheria toxin: at low pH the toxin induces ion channels on cells. - Papini, E (1988)
Diphtheria toxin (DT) in acidic media forms ion-conducting channels across the plasma membrane and inhibits protein synthesis of both highly and poorly DT-sensitive cell lines. This results in loss of cell potassium and in entry of both sodium and protons with a concomitant rapid lowering of membrane potential. The pH dependency of the permeability changes is similar to that of the inhibition of cell protein synthesis. DT-induced ion channels close when the pH of the external medium is returned to neutrality and cells recover their normal monovalent cation content. Similar permeability changes were induced by two DT mutants defective either in enzymatic activity or in cell binding, but not with a mutant defective in membrane translocation. The implication of these findings for the mechanism of DT membrane translocation is discussed.